The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/adem.201700197
|View full text |Cite
|
Sign up to set email alerts
|

Small Y Addition Effects on Hot Deformation Behavior of Copper‐Matrix Alloys

Abstract: Hot deformation behavior of two alloys, Cu-Zr and Cu-Zr-Y is studied by compression tests using the Gleeble-1500D thermo-mechanical simulator. Experiments are conducted at 550-900 C temperature and 0.001-10 s À1 strain rate. The true stress-true strain curves are analyzed, and the results show that the flow stress strongly depends on the temperature and the strain rate. Furthermore, both alloys behave similarly when the flow stress increases with higher strain rate and lower temperature. Based on the dynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Many studies have shown that the addition of rare‐earth elements can promote precipitation. [ 43 ] To study the influence of adding Ce to Cu–Ti–Ni–Mg alloys on precipitation during hot deformation, FEI Tecnai F30 transmission electron microscope was used to analyze the microstructure of the alloys deformed at a strain rate of 0.001 s −1 and 750 °C. Figure shows the microstructure of the Cu–Ti–Ni–Mg alloy deformed at 0.001 s −1 strain rate and 750 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the addition of rare‐earth elements can promote precipitation. [ 43 ] To study the influence of adding Ce to Cu–Ti–Ni–Mg alloys on precipitation during hot deformation, FEI Tecnai F30 transmission electron microscope was used to analyze the microstructure of the alloys deformed at a strain rate of 0.001 s −1 and 750 °C. Figure shows the microstructure of the Cu–Ti–Ni–Mg alloy deformed at 0.001 s −1 strain rate and 750 °C.…”
Section: Resultsmentioning
confidence: 99%
“…and, as a consequence, to different experimental dependences of stresses on deformations. For example, such scatters for copper alloy samples are given in [87,88].…”
Section: Illustrative Numerical Examplesmentioning
confidence: 99%
“…For all these reasons, a single technique able to produce nanofoams with controlled properties, and different materials, is of certain interest. Various techniques have been employed for the synthesis of nanofoams, each one being usually suited for specific combinations of elements, morphologies, and average density ranges: chemical vapor deposition (CVD), [27][28][29] thermal evaporation for metallic foams, [30] sol-gel method for silica nanofoams, [31] CO 2 foaming processes [32] for polymer nanofoams, and aerosolassisted chemical vapor deposition for ceramic nanofoams. [33] Among these methods, pulsed laser deposition (PLD) stands out as a versatile and promising tool for nanofoam synthesis.…”
Section: Introductionmentioning
confidence: 99%